Formulation and evaluation of thermoreversible in Situ Gelling and Mucoadhesive Diltiazem Hydrochloride Liquid suppository - R. V. KENY; C. F. LOURENCO (International Journal of Pharma and Bio Sciences, 2010)
Objective of the present study was to develop and evaluate thermoreversible in situ gelling and mucoadhesive liquid suppositories to improve patient compliance and systemic absorption of diltiazem hydrochloride. Thermoreversible mucoadhesive liquid suppositories were prepared by adding mucoadhesive polymers to a formulation that contained pluronic F-127, pluronic F-68 and diltiazem hydrochloride. Mucoadhesive polymers such as Carbopol 974P, Polyox WSR-301, hydroxypropyl methylcellulose, polycarbophil and polyvinylpyrrolidone were investigated to modulate the gel strength and mucoadhesive force for diltiazem hydrochloride liquid suppository. Addition of these polymers reinforced the gel strength and the mucooadhesive force of the prepared liquid suppository formulation. Increasing the concentration of mucoadhesive polymers retarded the release of diltiazem hydrochloride from the pluronic gel. Carbopol and polycarbophil showed highest retardation of drug release than other polymers investigated. Diltiazem hydrochloride formulated as mucoadhesive thermoreversible poloxamer solution for rectal administration can have potential to avoid first-pass effect through oral route, improve the bioavailability of drug and it can be used as a safe and sustained release rectal delivery system to control severe post-operative pain.